PUBLIC POLICY AND PUBLIC ADMINISTRATION IN THE FIELD OF EDUCATION: A COMPARATIVE ANALYSIS OF UKRAINE AND POLAND - Dakal, Аllа (Public Management and Policy, 2026)
The article addresses the issues of public policy and public administration in the field of education in a comparative perspective of Poland and Ukraine, taking into account Ukraine’s European integration course and the current security, social and economic challenges. The methodological rationale for choosing Poland as a reference model for Ukraine is substantiated by the common post-socialist legacy combined with different stages of institutionalisation of European education policy standards. Drawing on an analysis of recent publications devoted to the governance of general secondary and higher education, international quality assurance standards, the role of local self-government bodies, and the ability of education systems to respond to migration and humanitarian crises, the paper identifies a set of common factors of public governance in education in Poland and Ukraine and delineates the key differences between them. It is noted that both countries are building their education systems, taking into account EU documents, OECD recommendations, Bologna Process requirements, and international quality indicators and international standards, albeit with different levels of involvement. It is shown that both countries share such factors as the Europeanisation of legal and managerial frameworks, the massification of education, gradual decentralisation, a declared focus on quality, the use of external evaluation instruments and a growing importance of the local level of governance. At the same time, it is argued that the Polish model is characterised by a higher degree of institutional stability, a more mature culture of evidence-based policy and the real autonomy of educational institutions and local self-government, whereas the Ukrainian system operates under conditions of fragmented regulation, severe resource constraints and war-related shocks. On this basis, the main problems of public education management in Ukraine are outlined and directions for the adaptive use of Polish experience related to the stabilization of educational policy are formulated. Such as: an external evaluation system, quality assurance mechanisms, basic financing models; support for decentralization through training and professionalization of local management teams, institutionalization of the quality assurance system, strengthening the management capacity of territorial communities, and meaningful integration of migration and language dimensions into educational policy through mechanisms developed in the education system for the integration of migrants and refugees.